Mixing environmental waste and banana stem waste into compost and chips in Sukamaju Village, Jonggol - Meliantari, Dian; Sugeng, Margono; Wahdiniawati, Siti Annisa (CV. Rayyan Dwi Bharata, 2025)
A beautiful green environment certainly makes the home environment beautiful. But lush trees and greenery also pose a problem if the litter is left scattered. Banana stem waste also adds to the waste in the environment. In addition to looking dirty, it can also invite the presence of insects, other animals that can be dangerous such as snakes. Residents can use dry leaf waste and banana stem waste into a valuable product. Dried foliage can be turned into compost, while banana stem waste can be processed into delicious chips. So the solution taken is to provide training on how to process environmental waste such as dry leaves, twigs and others into compost. The next training is to make chips from banana stalks. Then provide training on how to choose packaging and create attractive labels. Finally, the training determines the selling price of the product produced. The results of the training are compost products and chips as well as packaging for compost and chips that can be used by themselves or to start entrepreneurship to increase family income. In addition to products, residents' knowledge is increasing about choosing good packaging and how to determine the selling price of products.